(−)-Oleocanthal induces death preferentially in tumor hematopoietic cells through caspase dependent and independent mechanisms. Issue 21 (18th October 2022) - Pastorio, Chiara; Torres-Rusillo, Sara; Ortega-Vidal, Juan; Jiménez-López, M. Carmen; Iañez, Inmaculada; Salido, Sofía; Santamaría, Manuel; Altarejos, Joaquín; Molina, Ignacio J.
Abstract : Olive oil is a key component of the highly cardiovascular protective Mediterranean diet. Abstract : Olive oil is a key component of the highly cardiovascular protective Mediterranean diet. (−)-Oleocanthal (OLC) is one of the most interesting phenolics present in virgin olive oil, and is formed from secoiridoid ligustroside during the processing of olives to yield the oil. Anti-inflammatory and anti-oxidant properties were identified shortly after OLC isolation, followed by the discovery of anti-tumor activities in a few non-hematopoietic cell lineages. Because of the scarcity of tissues potentially targeted by OLC analyzed so far and the unresolved mechanism(s) for OLC anti-tumor properties, we used a panel of 17 cell lines belonging to 11 tissue lineages to carry out a detailed examination of targets and pathways leading to cell growth inhibition and death. We found that OLC inhibits cell proliferation and induces apoptotic death as revealed by sub-G1 cell cycle analyses and Annexin-V staining in all lineages analyzed except lung carcinoma cell lines. Hematopoietic tumor cell lines, untested until now, were the most sensitive to OLC treatment, whereas non-transformed cells were significantly resistant to cell death. The specificity of OLC-mediated caspase activation was confirmed by blocking experiments and the use of transfectants overexpressing anti apoptotic genes. OLC triggers typical mediators of the intrinsic apoptotic pathway such as production of reactive oxygen species and mitochondrial membrane depolarization (Δ ψ m ). Complete blockade of caspases, however, did not result in parallel abrogation of Annexin-V staining, thus suggesting that complex mechanisms are involved in triggering OLC-mediated cell death. Our results demonstrate that OLC preferentially targets hematopoietic tumor cell lines and support that cell death is mediated by caspase-dependent and independent mechanisms.